Characterization, compaction and CBR (ISC), by the DIRENG-ME-01/87 Method, carried out on typical Latosol from the Brazilian Midwest for an area at the Presidente Juscelino Kubitschek International Airport, Brasília / Distrito Federal (International Seven Journal of Multidisciplinary, 2024)
This work presents field and laboratory geotechnical studies, with emphasis on compaction tests according to the recommendations of the Test Method for Airport Infrastructure Works (AASHTO Method) and California Bearing Ratio (CBR) tests, with the aim of determining the CBR using the DIRENG-ME-01/87 method for subgrade material, which takes into account the CBR corresponding to 95% of the dry specific mass compacted at the Modified Proctor energy, resulting from the composition of the graph of the three compaction energies (normal, intermediate and modified). The study involved an extensive bibliographical survey, field and laboratory work with geotechnical tests, as well as the appropriate processing of the results obtained. The studies showed that the soils have visual tactile characteristics with a predominance of latosol type sandy-silty clay to red sandy-silty clay. In addition, classification by the Unified Soil Classification System (SUCS) showed a predominance of low plasticity silt (ML), but also by TRB (HRB) a predominance of clayey soils (A-7-5). The CBR values using the DIRENG-ME-01/87 method for the 18 samples studied ranged from 8.1% to 9.0%, with an average value of 8.7%, representing 61% of the average CBR value of the modified energy, which was 14%.